Investigation on the properties of SnxSb10Se90-x chalcogenide semiconductor - Sakrani, Samsudi; Belal Adam, Abdallah; Wahab, Yussof (Malaysian Solid State Science and Technology Society, 2002)
Studies on tin-antimony-selenium (TAS) system of SnxSb10Se90-x (x= 0, 5, 10, 12.5, 15, 20 and 30) have been carried out using XRD, XGT and DTA and density measurement, so as to elucidate the structural states and thermal properties. XRD analysis for x= 0, 5, 10 and 12.5 gave an indicative amorphous phase, while that of the samples with x= 15, 20 and 30 maintain the crystalline structures. These were further confirmed by XGT results, which measured the weight percentages and elemental mapping of the samples. It was also observed that x plays important roles in determining the thermal quantities and density of the samples.